Automatic keyword classification for information retrieval - Sparck Jones, Karen (London: Butterworths, 1971)
This book is primarily a research monograph, in which the discussion of the main topics has been broadened so that they are related to their surrounding context in information retrieval as a whole. It is not a textbook, and no attempt has therefore been made to justify the choice of topic or account for the use of certain concepts, or to provide an elementary description of either.
Index and Bibliography references.
aia 23/6/17
Keywords: Automatic indexing; Information storage and retrieval systems